Exploring challenges of food delivery riders in the gig economy - a conceptual model / Aziemah Ahmad and Emi Normalina Omar - Ahmad, Aziemah; Omar, Emi Normalina (Universiti Teknologi Mara Selangor, 2023)
The widespread use of smartphone apps and online ordering has contributed to a significant increase in the meal delivery sector in recent years. These riders have flexible job alternatives because of the gig economy; nevertheless, there are drawbacks as well. Food delivery riders play a crucial role in ensuring the smooth and efficient delivery of food to customers. However, not all food delivery procedures go smoothly because there are a number of obstacles and problems that food delivery riders have to deal with before the food is delivered to the clients. Thus, the purpose of this research is to identify the factors that lead to the issues and challenges that urban area of food delivery drivers encounter. A conceptual model has been laid out based on the findings of the interview conducted with 10 food delivery riders in order to accomplish this research based on data saturated. According to the research, there are four main factors that lead to issues and challenges for food delivery riders: time constraints, fraudulent consumers, dangerous behaviour, and system problems. Future research can be shaped by the suggested conceptual framework.